2020
DOI: 10.1088/1742-6596/1567/3/032057
|View full text |Cite
|
Sign up to set email alerts
|

The potential effect of high flavonoid soybean diversification products through tempe flour substitution

Abstract: Nowadays, overconsumption of junk food and sedentary lifestyle lead to the development of various diseases. Legumes intake has been known to support one’s health since it’s contain various nutrients and bioactive compounds that’s beneficial for health. One of the most consumed legumes is soybean. In Indonesia, soybean usually consumed as tempe and tahu (tofu). Tempe contain numerous nutrients, for example carbohydrates, fats, proteins, minerals, dietary fibers, vitamins, and antioxidants. Therefore, tempe can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Besides being the main protein source, soy-based tempe has been developed as a carbohydrate substitute in the form of flour. It has been found that tempe flour-based products have higher flavonoid content than wheat-based products ( 14 ). Because of its high glutamic acid and protein content, overripe tempe is utilized both as a source of umami flavor and protein in porridge for children under five years old to help overcome children’s malnutrition ( 15 ).…”
Section: Soy-based Tempe In Generalmentioning
confidence: 99%
“…Besides being the main protein source, soy-based tempe has been developed as a carbohydrate substitute in the form of flour. It has been found that tempe flour-based products have higher flavonoid content than wheat-based products ( 14 ). Because of its high glutamic acid and protein content, overripe tempe is utilized both as a source of umami flavor and protein in porridge for children under five years old to help overcome children’s malnutrition ( 15 ).…”
Section: Soy-based Tempe In Generalmentioning
confidence: 99%
“…The content of bioactive compounds in it, such as isoflavones, sterols, and fiber from the oligosaccharide group, can have a positive impact on health and prevent the onset of degenerative diseases. Tempeh also contains vitamin B12, probiotic bacteria, and a source of antioxidants derived from isoflavone compounds and Superoxide dismutase (SOD) [2].…”
Section: Introductionmentioning
confidence: 99%